Foreign patenting in Germany: 1877 - 1932 - Harald Degner; Jochen Streb (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2010)
In this paper, we use both patents' individual life span and foreign patenting activities in Germany to identify the most valuable patents of the 21 most innovative countries (except for Germany) from the European Core, the European periphery and overseas between 1877 and 1932. Our empirical analysis reveals that important characteristics of the international distribution of foreign patents are time-invariant. In particular, the distribution of foreign patents across countries in the late nineteenth and early twentieth centuries was as highly skewed as it was in the late twentieth century - and even dominated by the same major research economies. Our analysis suggests that firms' technological advantages were influenced both by exogenous local factors, such as the countries' resource endowment, and by endogenous factors, such as the national education and research system or the countries' actual stage of economic development.
urn:nbn:de:bsz:100-opus-5078
Keywords: 330; Patent; Technologietransfer; Wirkungsanalyse; Wirtschaftswachstum; Theorie